Edukasi Dengan Pendekatan Fisioterapi Komunitas pada Komunitas Hipertensi Di Wilayah Puskesmas Gajahan Surakarta - Muhammad Shamil Muwaffaq; Farid Rahman; Amalia Faradilla Rahim (Pusat Riset dan Inovasi Nasional, 2023)
Kauman is a village located in the Kliwon Market district of Surakarta. Hypertension is one of the most dangerous health problems in the world because it is a major risk factor that leads to cardiovascular diseases such as heart attack, heart failure, stroke and kidney disease. The goal of this program is to prevent, and control high blood pressure. The method used in this community service is health promotion related to hypertension targeted participants Posyandu Lansia Chasanah which is located in Kelurahan Kauman. The writer uses the lift to find out the level of understanding of the participants of Posyandu Chasanah. The results of the lift showed a pre-test average of 9.49, whereas the post-test averaged 9.84, which means an improvement of 0.35. The minimum pre-test score is 7 and the post test score is 9. The minimum score has an increase of 2.